THE EFFECT STORYTELLING TO 2ND SEMESTER STUDENTS OF UNIVERSITY MUHAMMADIYAH TANGERANG - arjulayana, Arjulayana -; nargis, Nargis -; Putri, Bunga Malika (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
ABSTRACT Storytelling is an activity or activity to tell a story organize and attractively.  This research is aimed to discover the differences between students who given storytelling and the students who given conventional technique in improving students’ speaking skill. The research conducted to 2nd semester student from universitas Muhammadiyah Tangerang with the total sample is 56 students. The methodology of the research is quantitative approach with quasi experimental method. The researcher did 2 tests, consist of pre-test and post-test. This research was conducted of two classes, control class and experiment class. The result of the research shows that students who taught by using storytelling have higher score than the students who taught by using conventional technique. The students can explore their ideas well and more interested in learning speaking by using storytelling. As suggestion, the researcher hopes that the teachers must be able to choose appropriate technique and media in teaching English.